(3GdGbJUGO Gdcdj Hjf GdfXQjI hGdJWHjb (B:s (3CYeGd ehLgI CSFdI hJeGQjf eMdhdI (B/s - (3HQjHT, GdSYjOs ((3GdLRGFQ (B: s (3OGQ GdYdhe ddfTQ hGdJhRjY(B, s, 2007)
(3jMJhj Ydi JeGQjf NGUI HcjajI MSGH GdfTGW GdGbJUGOj ddeLJeY ef(B1 (3Edi (B13(3, JeGQjf NGUI HGdfehPL GdcdGSjcj ddJhGRf GdGbJUGOj Gdcdj ef(B14 (3Edi (B16(3, JeGQjf NGUI HOhGd GdGSJgdGc ef (B17(3Edi (B21(3, JeGQjf NGUI HOQGSI GdGSJKeGQ ef (B22(3Edi (B27(3, JeGQjf NGUI HOQGSI GdeVGYaGJ ef (B28 (3Edi (B35(3, JeGQjf NGUI HGdfehPL GdcjfRj ddJhGf GdGbJUGOj Gdcdj ef (B36 (3Edi (B41(3, JeGQjf YGeI eTJQcI Hjf GdaUhd ef(B42(3Edi (B59.s
(3HjHdjhZQGajG U(B.208s
Keywords: (3GdGbJUGO GdQjGVjs; (3GdGbJUGO Gdcdjs